Nanomaterials for biofouling and scaling mitigation of thin film composite membrane: a review - Ong, Chi Siang (Elsevier, 2016)
Biofouling and scaling are commonly encountered bottlenecks in large and small scale installations of membrane technology for surface-, waste- or seawater treatment. The phenomena can pose persistent operational challenge with substantial economic impacts if they are left unresolved. Effort has been made to reduce the tendency of these detrimental phenomena by improving membrane properties, optimizing operational conditions as well as establishing reliable pretreatment of the feed water. This review places a main focus on the recent advances of low biofouling and scaling thin film composite (TFC) membranes that are incorporated with different types of nanomaterials. In this contribution, the biofouling and scaling phenomena and their negative effects on TFC membranes are first discussed. The recent studies on the preparation of low biofouling and anti-scaling TFC membrane using different nanomaterials are then critically summarized. Current challenges to enhance membrane long-term stability, reliability, and cost efficiency are also highlighted. The applications of nanomaterials in membrane desalination are anticipated to improve resistance properties of TFC membranes against biofouling and scaling and further foster the innovation of sustainable membrane desalination technology.